Evaluation of Silicon and irrigation on three Safflower cultivars (Nexo Revista Científica, 2020)
This study was performed to evaluation of interaction of silicon application and irrigation on agronomic and physiologic traits of safflower at 2018 and 2019. The experiment was conducted as a split plot factorial based on randomized complete block design with 3 replications. The irrigation was main factor (0, 2 and 4 times during growth) and the sub-factor were silicon foliar application (at three levels: 0, 1 and 2 mM) and three safflower cultivars (Goldasht, Padideh and Golmehr). The studied traits were: number of seeds per boll and 1000-grain weight, number and weight of boll, number of lateral branches and branch diameter, plant weight and total plant weight, floret yield, grain yield, chlorophyll a and b, proline and antioxidant enzymes. According to results, treatments had significant effects on studied traits at 5 or 1% statistically level. 2 and 3 times irrigation led to 7 and 24% the increasing of seed yield in compare to control, respectively. It was obtained that 1 and 2mM silicon led to 25 and 15% the increase of seed yield in compare to control. Interaction between treatments showed that the highest seed yield (500g per m2) was observed by Goldasht cultivar under 4-time irrigation and 2mM silicon. Therefore, it can be suggested that Goldasht with 2 mM silicon be used to reduce the effects of dehydration.